2006
DOI: 10.1099/vir.0.81606-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a chimpanzee alphaherpesvirus

Abstract: Although both beta-and gammaherpesviruses indigenous to great-ape species have been isolated, to date all alphaherpesviruses isolated from apes have proven to be human viruses [herpes simplex virus types 1 (HSV1) and 2 (HSV2) or varicella-zoster virus]. If the alphaherpesviruses have co-evolved with their host species, some if not all ape species should harbour their own alphaherpesviruses. Here, the isolation and characterization of an alphaherpesvirus from a chimpanzee (ChHV) are described. Sequencing of a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 21 publications
4
30
0
Order By: Relevance
“…Our results indicate that all HSV-2v isolates harbor a specific UL30 molecular signature that perfectly matches a nucleotide segment in the ChHV UL30 gene. As previously reported, ChHV is a true chimpanzee simplex virus rather than a variant of human HSV transmitted to chimpanzees (28). Moreover, ChHV is closely related to, but different from, HSV-2, from which it is separated by a mean distance of ϳ8% (23).…”
Section: Discussionmentioning
confidence: 65%
“…Our results indicate that all HSV-2v isolates harbor a specific UL30 molecular signature that perfectly matches a nucleotide segment in the ChHV UL30 gene. As previously reported, ChHV is a true chimpanzee simplex virus rather than a variant of human HSV transmitted to chimpanzees (28). Moreover, ChHV is closely related to, but different from, HSV-2, from which it is separated by a mean distance of ϳ8% (23).…”
Section: Discussionmentioning
confidence: 65%
“…Limited phylogenetic analysis of an alphaherpesvirus (ChHV) isolated from a chimpanzee placed it within a hominid virus clade as expected based on host phylogeny [2]. However, ChHV and HSV2 are more closely related to each other than either is to HSV1.…”
mentioning
confidence: 99%
“…ChHV strain 105640 was originally isolated in 2004 from a chimpanzee ( Pan troglodytes ) during an outbreak of oral lesions in a captive colony and was propagated in Vero cells as described [2]. Viral DNA was purified from infected cells on NaI gradients, sequencing was performed on a Genome Sequencer 20 (Roche) using the manufacturer’s Shotgun Sequencing protocol, gaps were closed using a conventional shotgun library, and the sequence was assembled and analyzed as described previously [5].…”
mentioning
confidence: 99%
“…Analysis of the genome of a chimpanzee herpesvirus (ChHV) isolated in 2004 showed that HSV-2 was more closely related to ChHV than to HSV-1 (13,14). Phylogenetic analysis suggested that HSV-2 might be the original human herpes simplex virus (14).…”
mentioning
confidence: 99%